Prevalence of Delayed Discharge Among Patients Admitted to the Internal Medicine Wards: A Cross-Sectional Study - Filippo Binda; Federica Marelli; Valeria Cesana; Veronica Rossi; Nadia Boasi; Maura Lusignani (Nursing Reports)
Background/Objectives: Hospital bed shortage is a widespread issue affecting healthcare systems globally, often exacerbated by bed-blocking, a phenomenon where patients remain hospitalized longer than medically necessary due to discharge delays. The aim of this study was to evaluate the prevalence of patients with bed-blocker status admitted to the internal medicine wards. Methods: This cross-sectional study was conducted at an academic tertiary-level hospital in Milan (Italy) from 1 January to 31 December 2023. All adult patients identified as ready for discharge by the bed management service, but whose actual discharge was delayed by more than 24 h, were included. Clinical data were retrieved from electronic medical and nursing records. This study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Results: Out of 2480 admissions to the internal medicine wards, 147 patients (5.9%) experienced delayed discharge. The median hospital length of stay was 22 days (IQR: 15.0–33.0); the median duration of appropriate stay was 6 days (IQR: 2.0–13.0), and the median length of delayed stay was 14 days (IQR: 7.0–21.0). Waiting for transfer to lower-intensity care facilities was the primary cause of delayed discharge. Complications during delayed stays included delirium (31.3%) and hospital-acquired infections (35.4%), particularly urinary tract infections (17.7%). Logistic regression identified older age (≥75 years), extended hospital length of stay, emergency admissions, and discharge to long-term care as independent predictors of bed-blocker status. Conclusions: This study highlights delayed discharges as a significant issue in internal medicine wards, driven by advanced age, caregiver absence, and high dependency in activities of daily living.